ENHANCEMENT OF THE NUTRITIONAL AND INCOME OF THE MRAWAN VILLAGE COMMUNITY THROUGH ECO-FRIENDLY QUAIL POULTRY LIVESTOCK AT LOW COST - Wenny Maulina; Yuda Cahyoargo Hariadi; Arry Yuariatun Nurhayati; Misto Misto (UNEJ e-Proceeding, 2022)
The yard can provide great benefits for the community, because it can be planted with vegetables, fruits and spices such as turmeric, lemongrass, etc. The yard can also be used as a source of animal protein and an additional source of family income. Quail farming is an alternative for producing eggs which is quite productive in addition to laying hens and ducks. The advantages of quail cultivation are having a small body size and weighing about 130 grams, a short life cycle, high egg productivity (in the peak period of daily egg production it can produce about 90% of the total population in the cage), low feed intake (about 20 grams/quail/day), easy to cultivate and does not require a high investment. Quail can give results in the form of daily egg production and/or meat from rejected quail (quail that have stopped laying eggs or egg productivity that begins to decline after about 8 months of age). Quail cultivation from the yard of the house can be used to maintain approximately 25 quails. Based on these advantages, quail cultivation in the yard can provide family income and increase nutrition. Keywords: quail, yard, nutritional, income